Knowledge and Attitudes of Pregnant Women during Antenatal Care Visit at Abi Ummi DW Sarmadi Clinic Palembang Relationship Knowledge and Attitude of Pregnant Women Against Antenatal Care Visit In Abi Ummi DW Sarmadi Clinic Palembang - Erike Septa Prautami (Institute of Computer Science (IOCS), 2018)
Background Antenatal care is an important way to monitor and support and detect the health of pregnant women with normal mother normal pregnancy. The objective of this study is to know the relationship of knowledge and attitudes of pregnant women against antenatal care visit in Abi Ummi DW Sarmadi Clinic Palembang. The Methods used in this research are analytic surveys with the approach of